The Effect of Plantarflexor Strength Training on Gait Biomechanics in Healthy Old Adults - Tatarski, Rachel L. (East Carolina University, 2013)
Locomotion is an important and inherent part of daily life and is integral in maintaining an independent lifestyle, especially in older adults whose functional capacity has declined. Physiological changes with aging, including loss of muscle mass, strength and power are manifested in walking, notably at the ankle joint. Old adults exhibit decreased power of the plantarflexors and increased power of the hip extensors. This distal to proximal shift in function could be due to plantarflexor weakness, so strengthening the plantarflexors may help reverse the negative physiological effects of aging and help preserve functional capacity in old adults. The purpose of this study was to determine the effect of plantarflexor strength training on gait biomechanics during level walking at a self-selected, a safe maximum and a standard speed of 1.5 m/s in healthy old adults. A total of 12 healthy adults between the ages of 65 and 85 participated in this study (6 strengthening, 6 stretching). After baseline tests, the strengthening group performed resistance exercises for gastrocnemius and soleus muscles and the stretching group stretched them three times per week for 12 weeks. All subjects underwent gait assessments and maximal strength testing at the beginning and end of the 12 week training period. A 2 by 2 analysis of variance was used to determine significant interactions and main effects with an alpha level of p<0.05. Plantarflexor strength increased in the strengthening group but not for the stretching group. Compared to the pretest, the subjects in the stretching group walked significantly faster, took longer strides, increased peak plantarflexor torque and ground reaction force during the self-selected walking condition, while there were no changes in the strengthening group. Based on these results, a twelve week strength training program does not affect the gait biomechanics of healthy old adults while stretching does produce some changes to the gait biomechanics of healthy old adults.
Keywords: Kinesiology; Biomechanics; Gait; Plantarflexor; Strength; Aging; Gait disorders in old age; Leg--Muscles